Elicting public support for greening the electricity mix using random parameter techniques - Peter Grösche; Carsten Schröder (Kiel University, Department of Economics, 2010)
With its commitment to double the share of renewables in electricity generation to at least 30% by 2020, the German government has embarked on a costly policy course whose public support remains an open empirical question. Building on ample household survey data, we trace peoples' willingness-to-pay (WTP) for various fuel mixes in electricity generation, and capture preference heterogeneity among respondents using random parameter techniques. Based on our estimates, we infer price premia that can be charged for specific electricity mixes while ensuring that a majority of people still supports the policy. Despite that people's WTP for electricity is positively correlated with the share of renewables in electricity generation, our results imply that the financial scope for subsidizing renewables is virtually exhausted.
Keywords: 330; green electricity; willingness-to-pay; preference heterogeneity; policy evaluation